2001
DOI: 10.2527/2001.7951201x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary oils and alpha-tocopheryl acetate supplementation on lipid (TBARS) and cholesterol oxidation in cooked pork.

Abstract: The effect of n-3 fatty acid-enriched diets (in the form of 0.5% linseed oil with either 1.5% sunflower oil or 1.5% olive oil) and alpha-tocopheryl acetate supplementation (200 mg/kg feed) on lipid oxidation (thiobarbituric acid-reactive substances, TBARS) and cholesterol oxide products (COPS) in cooked pork was investigated. Longissimus muscle was studied. Meat from pigs fed 0.5% linseed oil-enriched diets had a higher proportion of n-3 fatty acid than meat from pigs in other dietary groups in neutral (P < 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
48
2
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(65 citation statements)
references
References 31 publications
11
48
2
3
Order By: Relevance
“…After 9 days of storage at 48C, the total COP values were two or three times higher than they were on day 3. Similar data were described previously by Rey et al (2001), who found that the COPs in pork significantly increased during refrigerated storage.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…After 9 days of storage at 48C, the total COP values were two or three times higher than they were on day 3. Similar data were described previously by Rey et al (2001), who found that the COPs in pork significantly increased during refrigerated storage.…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, several studies have suggested that cholesterol oxidation is higher in cooked meat from pigs fed n-3-enriched diets, which may lead to more undesirable health effects than potential benefits (Rey et al, 2001). Vitamin E administered to animals has been shown to be effective in reducing COP contents in cooked meat from pigs (Rey et al, 2001;Eder et al, 2005) and chickens (Grau et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of whole linseed in increasing the PUFA and a-linolenic acid contents in the meat has been previously reported by several studies on both rabbit (Bernardini et al, 1999;Dal Bosco et al, 2004) and other species (Mattews et al, 2000;Riley et al, 2000;Rey et al, 2001). Moreover, Colin et al (2005) recently proposed the use of a commercial feed ingredient (Tradi-Lin ® ) containing extruded linseed to increase the a-linolenic acid contents of rabbit meat.…”
Section: Meat Qualitymentioning
confidence: 83%
“…The dietary use of linseed in animal feeds has been proposed by many authors as a vegetable alternative to fish oil or fish meal, to raise the content of n-3 polyunsaturated fatty acids (n-3 PUFA), and mainly a-linolenic acid (C18:3 n-3) in poultry (Ajuyah et al, 1993), pork (Mattews et al, 2000;Rey et al, 2001;Wood et al, 2003) and rabbit meat (Bernardini et al, 1999;Dal Bosco et al, 2004;Colin et al, 2005). Some authors also reported beneficial effects of linseed on performance, milk composition and viability of the progeny in rabbit does.…”
Section: Introductionmentioning
confidence: 99%
“…Pentadecanoic acid (C15:1) (Sigma, Alcobendas, Madrid) was used as internal standard. Fatty acid methyl esters were identifi ed by gas chromatography using a 6890 Hewlett Packard (Avondale, PA, USA), gas chromatograph equipped with a fl ame ionization detector and a capillary column HP-Innowax (30 m × 0.32 mm × 0.25 µm cross-linked polyethylene glycol) as described by Rey and Lopez-Bote (2001). Concentration of trans fatty acids in fats used in this experiment (hydrogenated palm fat, lard, olive oil and sunfl ower oil) was quantifi ed by gas chromatography using a 6890 Hewlett Packard (Avondale, PA, USA) gas chromatograph equipped with a fl ame ionization detector and a capillary column (Supelco SP2340 60 × 0,25 mm × 0,2 µm fi lm thickness).…”
Section: Slaughter Sample Collection and Chemical Analysismentioning
confidence: 99%